2021
DOI: 10.1039/d0cp05737a
|View full text |Cite
|
Sign up to set email alerts
|

Redox-couple investigations in Si-doped Li-rich cathode materials

Abstract: Si doping improves the electrochemical behavior of Li-rich cathodes during the activation cycle by changing the operative redox couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…[15] It is confirmed that the undesirable structural degeneration starts from the surface to the bulk for Li-rich Mn-based oxides. [16,17] One recent study declares that localized O 2 acts as the oxidation product of lattice oxygen. [18] Compared with the material bulk, O 2 first escapes from the surface, thus exacerbating the lattice destruction of the material surface.…”
mentioning
confidence: 99%
“…[15] It is confirmed that the undesirable structural degeneration starts from the surface to the bulk for Li-rich Mn-based oxides. [16,17] One recent study declares that localized O 2 acts as the oxidation product of lattice oxygen. [18] Compared with the material bulk, O 2 first escapes from the surface, thus exacerbating the lattice destruction of the material surface.…”
mentioning
confidence: 99%
“…17 Compared to the abundance of metal cations available for doping, the existing catalyst modification studies on doping of non-metal cations are less extensive and mostly focus on the elements B, 18,19 N, 20,21 P 22,23 and Si. 24,25 On the other hand, anionic doping has also been used in recent years to create OVs and generates several interesting properties and basic anions available for doping are essentially non-metal anions. 11,12,26 For example, when Cl À is substituted for O 2 À , metal-oxygen covalency may increase, which is beneficial for charge transfer in electrocatalytic processes.…”
Section: Choice Of Dopant Ionsmentioning
confidence: 99%
“…In fact, partial substitution of inactive Ti in the Na‐layered oxides has been studied by a few groups in Na layered oxides and shown to have positive outcomes in terms of lessening structure evolution, [ 21 ] reducing lattice strain, [ 22 ] increasing voltage/capacity retention, [ 23 ] and improving reversibility of TM/O migration during sodiation/de‐sodiation process. [ 24 ] A few studies in Li‐rich layered oxides have indicated that Si in TM sites can reduce the O 2p band of the Fermi level, [ 25 ] promote the formation of oxygen vacancies, [ 26 ] and decrease the covalency degree between TM‐O allowing greater reversibility of anionic redox. [ 27 ] However, to our best knowledge, there is no report on the role of Si as dopants in Na layered oxides.…”
Section: Introductionmentioning
confidence: 99%